IMPLEMENTASI ANGGARAN PRODUKSI DALAM MENINGKATKAN EFISIENSI OPERASIONAL PERUSAHAAN - Fadillah Syafitri; Ayu Hani Marsani Tanjung; Zahir Muhammad Fadhilah Harahap; Dini Vientiany (CV. Denasya Smart Publisher, 2026)
This study aims to analyze how production budget implementation helps companies achieve operational efficiency through planning, controlling, evaluating, and using information technology. In this study, fifteen relevant research documents were reviewed to investigate the relationship between production budget implementation and operational efficiency improvement. The results of the analysis show that realistic production budget planning helps reduce input wastage from the beginning of the process. Comparison between budget and realized costs enables cost control to find variations that impact the efficient use of raw materials and labor. Furthermore, evaluation of these variations becomes a continuous operational learning mechanism that improves budget accuracy in the following period. Through the provision of fast, accurate and easily accessible data, information technology assists budget execution. Therefore, this study shows that the production budget is a strategic management tool that can sustainably improve the operational efficiency of the company. This is because operational efficiency depends not only on cost savings, but also on the implementation of a structured and customizable budget cycle.